Critical nitrogen dilution curve for estimating nitrogen nutrition index of common beans - Soratto, Rogério P. [UNESP]; Sandaña, Patricio; Sousa, Westefann S. [UNESP]; Fernandes, Adalton M. [UNESP]; Ciampitti, Ignacio A. (Elsevier, 2025)
Context or problem: Common beans (Phaseolus vulgaris L.) are a key crop in the global diet and nitrogen (N) fertilization is a critical management factor. Therefore, it is essential to develop a critical N dilution curve (CNDC) for common bean in order to improve N fertilization management. Objective or research question: The aims of this study were to quantify the CNDCs using a Bayesian statistical approach and calculate the N nutrition index (NNI) as a diagnosis metric for the attainable seed yield. Methods: Two field experiments were conducted in southeastern Brazil (Botucatu, São Paulo), evaluating three common bean cultivars (IPR Andorinha, IPR Campos Gerais, and TAA Dama) and three N fertilization rates (0, 60, and 120 kg N ha⁻¹). Aboveground dry matter (DM) biomass (W) and plant N concentration (%N) were determined at six sampling dates during the crop cycle. Results and conclusions: In both experiments, seed yield was influenced by N rate (p < 0.01), but neither by cultivar nor by cultivar × N rate interaction. A generic CNDC [Nc (%) = 4.72 W⁻0.32] was determined with reduced uncertainty in its parameters. A significant relationship (p < 0.05; R2 = 0.74) was obtained between the relative seed yield and the integrated NNI (NNI-int) calculated with the generic CNDC. The instantaneous NNI measured between pre-flowering (R5) and pod formation (R7) growth stages was identified to be a reliable predictor of relative seed yield. Implications or significance: Therefore, the generic CNDC and the determination of NNI are valuable tools for diagnosing N nutritional status and improving N fertilization management in common bean crops.
Keywords: Bayesian; N content; N management; NNI; Phaseolus vulgaris; Relative yield